Synthesis of transition metal nanoparticles deposited in KNBO3 and the evaluation of the catalytic effect on the evolution of hydrogen from NABH4 - Reis, Tulho Martins dos; Alves, Aléxia Caroline de Castro; Silva, Victor Nogueira da; Lopes, Renata Pereira Moreira (Brazilian Journal of Production Engineering, 2023)
From the hydrolysis of NaBH4, there is the evolution of H2, which is a spontaneous and kinetically slow process. Therefore, transition metal nanoparticles (NPs) deposited in KNbO3 can be used as catalysts. Thus, the objectives of the present work were the development of catalysts for the deposition of transition metal NPs in KNbO3 and the evaluation of the influence on the evolution of H2 from NaBH4. The synthesis of the support occurred via the hydrothermal route, while that of the NPs occurred via reduction of the precursor salt solution. Regarding the NPs evaluated (Pt, Pd, Ni, Au and Co), the best effects observed were for Pt and Ni. Regarding the bimetallic composition, the best effect was for the 1:3 composition (Ni:Pt, mol/mol). The process efficiency increased with increasing support dosage and temperature. It is concluded that it was possible to develop promising materials based on niobium, the largest world reserve of which is found in Brazil, for use in the evolution of hydrogen.
Keywords: Hydrogen Evolution; Potassium Niobate; Nanoparticles; Sodium Borohydride